2015
DOI: 10.1016/j.cognition.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ representations of others’ goals: Representing approach over avoidance

Abstract: Goals fall into two broad types – approach and avoidance. Research on infants’ early goal understanding has focused only on approach goals, usually assuming that infants will encode an ambiguous display where an actor picks one object over another as the actor wanting to approach the former rather than avoid the latter. We investigated infants’ understanding of approach and avoidance separately by presenting 7-month-olds with a hand either consistently approaching, or consistently avoiding, an object. Infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…During the first postnatal year, infants have the components of what would be needed to generate goal-based predictions. Visual habituation experiments have indicated that infants encode the goal structure of reaching actions by 6 months of age (e.g., Biro & Leslie, 2007; Feiman, Carey, & Cushman, 2015; Luo & Johnson, 2009; Woodward, 1998, 1999), and as described earlier, infants, visually anticipate reaching movements between 6 to 8 months (Gredebäck & Melinder, 2010; Kanakogi & Itakura, 2010; Kochukhova & Gredebäck, 2010; Rohlfing et al, 2012). When do infants put these two components together?…”
Section: Introductionmentioning
confidence: 68%
“…During the first postnatal year, infants have the components of what would be needed to generate goal-based predictions. Visual habituation experiments have indicated that infants encode the goal structure of reaching actions by 6 months of age (e.g., Biro & Leslie, 2007; Feiman, Carey, & Cushman, 2015; Luo & Johnson, 2009; Woodward, 1998, 1999), and as described earlier, infants, visually anticipate reaching movements between 6 to 8 months (Gredebäck & Melinder, 2010; Kanakogi & Itakura, 2010; Kochukhova & Gredebäck, 2010; Rohlfing et al, 2012). When do infants put these two components together?…”
Section: Introductionmentioning
confidence: 68%
“…One possibility is that younger children may have trouble reasoning about people expressing a dispreference-they inferred that someone who expressed a positive attitude about an action would engage in that action, but they did not predict that someone who expressed a negative attitude about an action would avoid that action. In line with this possibility, there is work demonstrating that young toddlers struggle more with inferring dispreference than preference (Feiman, Carey, & Cushman, 2015). However, we believe that this is fairly unlikely for two reasons: first, given that the children tested here were much older than toddlers (i.e., 4-to 6year-olds) and that, in general, even infants and young children are attentive to others' negative affect and use it to guide their own behavior (for review, see Vaish, Grossmann, & Woodward, 2008), we think it is highly unlikely that children are generally unable to make predictions based on dispreference.…”
Section: Discussionmentioning
confidence: 97%
“…One such study might be to search for evidence for negation functions that do not involve crossing out an option -for example, could Griffin learn two rules, that X predicts something on the left and that anything that is not an X predicts something on the right? Interestingly, several attempts to find such behaviour in human infants have failed -they learn the affirmative rule but not the negative one (e.g., Feiman et al, 2015;Hochmann et al, 2018). Similarly, could Griffin learn a rule conditioned on the relation of exclusive or?…”
Section: What Representations/computations Underlie Griffin's Success?mentioning
confidence: 99%